2011
DOI: 10.3168/jds.2010-3839
|View full text |Cite
|
Sign up to set email alerts
|

The composition of interfacial material from skim milk foams

Abstract: The foaming properties of skim milk vary with temperature of foaming in the range from 5 to 85°C, with foams of maximum stability being formed at approximately 45°C. This paper reports the significance of different milk fractions in the foam and concludes that the micellar casein fraction plays an important role in stabilization of milk foam formed at higher temperatures. This finding was supported by the fact that added calcium chloride increased and calcium-chelating agents decreased foam stability. These ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
4
16
0
Order By: Relevance
“…Protein is considered to be excellent foaming agents based on their good adsorption toward the air-water interface, properties of steric stabilization and electrostatic stabilization, and their tendency to form structural coherence (Murray, 2007). It has been proved the that the major composition of milk foam is casein (Kamath et al, 2011).…”
Section: Milk Foam Compositionmentioning
confidence: 99%
See 4 more Smart Citations
“…Protein is considered to be excellent foaming agents based on their good adsorption toward the air-water interface, properties of steric stabilization and electrostatic stabilization, and their tendency to form structural coherence (Murray, 2007). It has been proved the that the major composition of milk foam is casein (Kamath et al, 2011).…”
Section: Milk Foam Compositionmentioning
confidence: 99%
“…An investigation carried out by Kamath (2011) Mohanty et al (1988) on the aspect of temperature where their work showed that 25º C is the minimum temperature for milk to foam, and 40º C is the optimum temperature; they also offered valuable data indicating that the fat content has a negative effect for milk to foam. Kamath et al (2008) explored the influence of temperature on the foaming properties of a variety of milk and concluded that 45º C is the most optimum temperature for the skim milk foam stability.…”
Section: Influence Of Electric Charges On the Foaming Properties Of Milkmentioning
confidence: 99%
See 3 more Smart Citations